Exploring the BIM and lean synergies in the Istanbul Grand Airport construction project - Arayici, Yusuf; Koseoglu, Ozan; Sakin, Mehmet; Sakin, Mehmet (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose The purpose of this paper is to develop a solid understanding of how integrated building information modeling (BIM) is implemented in a mega project such as the (Istanbul Grand Airport IGA) construction project, which is the main case study in the research methodology. Design/methodology/approach The paper examines and identifies the lean efficiency gains achieved in the IGA project and highlights the synergies between BIM and lean concepts based on the facts and figures from the case study analysis. In complex projects, there is a vital need for a comprehensive approach that would enable successful managing of design and construction information via accurate modeling, collaboration and integration throughout the project lifecycles covering various disciplines. Findings The research findings in the paper make a significant impact in understanding the strategic perception for BIM as a new way of working methodology for the construction industry in Turkey, since the IGA project has become not only a key learning hub for the Turkish construction industry, but also a global landmark for digital construction and project delivery. In addition it proves the mutual synergies between BIM and lean practices. Originality/value The IGA project is a mega-scale airport construction project with features beyond building industry challenges, and it should be designed and constructed with tight deadlines and budgets and be operated afterwards in an effective and efficient way. Can lean and BIM help for timely and on-budget completion of the project and could they support the management of the airport facility after handover? The paper also discusses the lean and BIM implementation in the project in relation to the BIM Level 3 requirements.
Keywords: Scheduling; Case study; Project management; Strategic management; Engineering; Building information modelling